Speaking positions: Zimbabwean women's writing in English and the disease, pain and trauma paradigm - Ngoshi, Hazel T.; Zhou, Sindiso (Unisa Press, 2016)
This article critiques the disease, pain and trauma paradigm in Zimbabwean women’s writing in English. In discussing Virginia Phiri’s Desparate, Lutanga Shaba’s Secrets of a woman’s soul, and Valerie Tagwira’s The uncertainty of hope, the article becomes a project of analysing the traumatic legacies of the female experience in Zimbabwe. By locating the analysis of the sample female-authored texts in the context of significant political, social and economic experiences in the postcolony, the article reflects on the ramifications of experiencing pain and trauma in a culture where no one is supposed to remember what they saw or experienced. The authors posit in this article that by creating narratives of disease, pain and trauma, Zimbabwean women have crafted a cultural speaking position from which to testify about cultural and social unspeakable. The argument in this article is that in placing the woman at the centre of the drama of pain and trauma, Zimbabwean women writers have feminised pain and trauma representation will increasingly become poetic, as Zimbabwean women’s writing in English is developing into testimonial practices, giving birth to a cultural language of trauma.